2007
DOI: 10.1177/1358863x07082720
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of 1-year optimal medical treatment with and without additional PTA on inflammatory markers of atherosclerosis in patients with PAD. Results from the Oslo Balloon Angioplasty versus Conservative Treatment (OBACT) study

Abstract: Abstract:The influence of optimal medical treatment (OMT) with or without additional percutaneous transluminal angioplasty (PTA) on vascular inflammation in peripheral arterial occlusive disease (PAD) patients was investigated. Patients with intermittent claudication (IC) and angiographically verified PAD were randomized to OMT (n ϭ 28) or OMT ϩ PTA (n ϭ 28) and followed for 12 months. Ankle-brachial index (ABI), treadmill walking distances (WD), visual analogue scale (VAS), and blood sampling for the determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…One trial reported 'few' complications 19,20 and the other four trials three, four, six and seven complications respectively 13,21 -23,25 . These complications consisted primarily of haematomas, but bleeding, artery dissections and artery rupture also occurred.…”
Section: Complicationsmentioning
confidence: 97%
See 4 more Smart Citations
“…One trial reported 'few' complications 19,20 and the other four trials three, four, six and seven complications respectively 13,21 -23,25 . These complications consisted primarily of haematomas, but bleeding, artery dissections and artery rupture also occurred.…”
Section: Complicationsmentioning
confidence: 97%
“…Two trials compared PTA plus ET advice with ET advice alone 15,16,19,20 , four compared PTA with SET 13,18,22 -24 , two compared PTA plus SET with SET 21,24 and two compared PTA plus SET with PTA 24,25 ( Table 4). Table 5 summarizes the diverse exercise programmes varying from home-based exercise without supervision 15,16,19,20 to SET programmes 13,18,21 -25 .…”
Section: Interventionsmentioning
confidence: 99%
See 3 more Smart Citations